Hematological and molecular characterization of beta-thalassemia/HB Tak compound heterozygote - Charoenkwan P. (2014)
We report a case of β-thalassemia/Hb Tak compound heterozygote. The 7 year-old Thai boy presented with plethora since birth. Hemoglobin electrophoresis showed a major band between Hb A2 and Hb F and absent Hb A. DNA sequencing study demonstrated an AC insertion at the terminal codon of the β-globin gene. The clinical feature of polycythemia reflected a high oxygen affinity of Hb Tak.